(untitled) - Gunther, H. (Chichester, UK, 1995)
The book provides a comprehensive introduction to the basic of technique combined with its more advanced applications to organic chemistry. It includes recent important advances in n.m.r. spectroscopy, two-dimensional methods, an elarged treatment of Fourrier transform methods, an introduction to the product operator formalism of modern pulse n.m.r., the description of gradient enhanced experiments and a new section on solid state n.m.r.
Các phương pháp quang phổ
Keywords: Nuclear magnetic resonance spectroscopy